THE REPRESENTATION OF MEDIA CRITICS IN DAN GILROY’S MOVIE NIGHTCRAWLER - Lambok Hermanto Sihombing (English Journal Literacy Utama, 2022)
News is one of the ways that people can stay informed about what is happening in the world. News can be both informative and interesting if the media and journalists construct it well. They collaborate to identify and generate hot and trending news. However, not all content is depicted accurately. They are both capable of manipulating and constructing news. This portrait is depicted in the film entitled Nightcrawler. This research aims to analyze the representation of how the media broadcasts phenomenal news, uncover how the character manipulates the story, and how both media and journalists get the advantages through the manipulated news they produce. In order to help the author doing this analysis, this research uses Media theory from John Hartley and Mise En Scene approach from Manon de Reeper. The result of this study indicates that this film represents the critics towards media such as how they, both media and journalists manipulate the news for their own advantages. At the end of this research, the author gives some personal reflections on the director's message in creating this film.